Green economy in the Western Balkans - Renko, Sanda; Pestek, Almir (Emerald Publishing Limited, 2017)
This multidisciplinary approach to the Western Balkans addresses topics from responsible business and ethics, innovation, corporate social responsibility, and new technology to human resources management. It is a theoretical and practical guide towards a sustainable future for the Western Balkans, showing drivers and barriers affecting the region in its effort to green its economy, and provides a systematic and holistic overview and critical examination of the situation in the region. Chapters explore a review of the literature and developing theory, and report empirical procedures. If the Western Balkan countries are following the industrialised states of Western Europe - which are now keen to develop in a sustainable manner, combining economic growth with social justice and improved environment - this work fills the growing need for more research and to expand the current knowledge base about environmental and development challenges, as well as the new, efficient and climate-neutral 'Green Economy' of this region.
Includes index.
Keywords: Balkan Peninsula -- Economic conditions.; Sustainable development -- Balkan Peninsula.; Environmental economics -- Balkan Peninsula.; elektronické knihy; electronic books